2006
DOI: 10.1124/jpet.105.098996
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of G Protein-Coupled Receptor Kinase (GRK) 3 and GRK2 in Down-Regulation of the α2B-Adrenoceptor

Abstract: Increasing the cellular levels of G protein-coupled receptor kinase (GRK) 2 or GRK3 renders the ␣ 2B -adrenoceptor (AR) more sensitive to agonist-induced down-regulation (J Pharmacol Exp Ther 312:767-773, 2005). However, an absolute requirement of GRK3 and GRK2 for ␣ 2B -AR down-regulation is controversial. In this study, using NG108 cells (endogenous ␣ 2B -AR), we provide strong evidence for a critical role of both GRK3 and GRK2 in down-regulation of the ␣ 2B -AR. Pretreatment of NG108 cells with 20 M epineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…Experimental examination of signaling processes at different spatial and temporal scales, for example the motion of individual molecules or the formation of particular signaling complexes, may require a more detailed model than that used here. Indeed, mechanisms other than variation in receptor or G-protein number, including the formation of multi-protein signaling complexes, clustering of receptors via dimerization or regulation of the numbers of other signaling proteins, may play roles in regulating crosstalk (Hall and Lefkowitz, 2002; Breitwieser, 2004; Woolf and Linderman, 2004; Desai et al , 2006). While we found it was not necessary to incorporate compartments to explain the signaling data explored here, compzartments may indeed exist and play a role at other levels.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental examination of signaling processes at different spatial and temporal scales, for example the motion of individual molecules or the formation of particular signaling complexes, may require a more detailed model than that used here. Indeed, mechanisms other than variation in receptor or G-protein number, including the formation of multi-protein signaling complexes, clustering of receptors via dimerization or regulation of the numbers of other signaling proteins, may play roles in regulating crosstalk (Hall and Lefkowitz, 2002; Breitwieser, 2004; Woolf and Linderman, 2004; Desai et al , 2006). While we found it was not necessary to incorporate compartments to explain the signaling data explored here, compzartments may indeed exist and play a role at other levels.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were processed for immunofluorescence as described previously (Desai et al, 2006). In brief, BE(2)-C cells were grown on poly-D-lysine-coated 20-ϫ 20-mm glass cover slips to 40 to 70% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…BE(2)-C cells were treated with EPI (0.3 M) or vehicle for 5 and 15 min. After the treatment, cells were processed for immunofluorescence as described previously (Desai et al, 2006). In separate samples, Sp-1 or Ap-2 were visualized with Alexa-488, whereas cell nuclei were stained with DAPI for visualization (blue).…”
Section: Regulation Of Grk3 Expression 53mentioning
confidence: 99%
“…G proteincoupled receptor kinase (GRK) 2 binds to and phosphorylates the agonist-activated ␣ 2 AR (Jewell-Motz and Liggett, 1996;Pao and Benovic, 2005), which subsequently interacts with arrestin (Wu et al, 1997;DeGraff et al, 2002;Wang and Limbird, 2002). GRK phosphorylation represents one major mechanism for ␣ 2 AR desensitization after agonist stimulation (Eason et al, 1995;Jewell-Motz and Liggett, 1996;Desai et al, 2006). Whether or not heterologous desensitization pathways Jewell-Motz et al, 1998;Liang et al, 1998) and sensitization pathways (Jones et al, 1987;Bylund, 1988, 1990) reported in vitro also contribute to desensitization of this receptor in vivo is not yet known.…”
mentioning
confidence: 99%